Anxiety sensitivity and suicidal ideation/suicide risk: A meta-analysis. - Ian H. Stanley; Joseph W. Boffa; Megan L. Rogers; Melanie A. Hom; Brian J. Albanese; Carol Chu; Daniel W. Capron; Norman B. Schmidt; Thomas E. Joiner (2018)
Suicide is a global public health concern. To inform the prevention and treatment of suicidality, it is crucial to identify transdiagnostic vulnerability factors for suicide and suicide-related conditions. One candidate factor is anxiety sensitivity (AS)-the fear of anxiety-related sensations-which has been implicated in the pathogenesis of a host of mental health outcomes, including suicidal thoughts and behaviors. Importantly, AS is distinct from trait anxiety and negative affectivity, highlighting its potential incremental utility in the understanding of psychopathology. Despite a burgeoning body of literature demonstrating that AS is linked to suicidal thoughts and behaviors, this research has yet to be synthesized.